Enhancing Stakeholder Communication and Management Strategies in Religious Tourism: A Case Study of Pura Parahyangan Agung Jagatkarta - Mariana Rista Ananda Siregar; Diffa Arcely Iskandar (Jurnal Komunikasi, 2025)
The utilization of places of worship as sustainable religious destinations necessitates not only the strategic management of communication with relevant stakeholders but also the preservation of cultural heritage, belief systems, and communal traditions. Furthermore, it requires safeguarding historical monuments and religious rituals while promoting environmental sustainability to maintain both the ecological integrity and the spiritual sanctity of the site. This research focuses on identifying the key stakeholders and evaluating the communication strategies employed between the management of the religious tourism site and other involved parties at Pura Parahyangan Agung Jagatkarta. Utilizing a sequential mixed-methods approach, which combines qualitative and quantitative research, data was gathered through comprehensive interviews and observations. This was further enriched by a SWOT analysis to establish effective management strategies. The Pentahelix model was applied to highlight the roles of five primary stakeholders: government, academia, community, business, and media. Findings from the IFAS and EFAS analyses suggest that while the natural allure of sites like Pura Parahyangan Agung Jagatkarta is significant, it must be matched by enhancements in infrastructure and accessibility. Managing religious tourism destinations such as Pura Parahyangan Agung Jagatkarta requires close collaboration among government, local communities, and businesses to optimize resources, improve infrastructure, and enhance accessibility. Sustainable management must address visitor surges, provide education on local rules and traditions, and preserve the sanctity and sacred atmosphere of the site. These measures ensure that the destination supports tourism while maintaining its cultural and religious values.